A SIMULATED ANNEALING APPROACH TO SCHEDULING: A CASE STUDY OF BOOTS CONTRACT MANUFACTURING (BCM) - DAR, UMAR B.T. (2017)
Scheduling is a crucial branch within operations management. Its application ranges from the manufacturing industry to the service industry. Traditionally, dispatching rules are used to optimise schedules to meet the organisations objectives. This research project focuses on the implementation of metaheuristics for scheduling, with particular focus on simulated annealing. The simulated annealing technique is developed in Visual Basic (VBA) embedded within Microsoft Excel. It is then evaluated on data obtained from Boots Contract Manufacturing (BCM), which is assumed to adhere to a single machine layout. The simulated annealing algorithm was tested in several variances. Two objective functions (minimum average tardiness and minimum number of tardy jobs) were implemented and their corresponding schedules were assessed against the other objective function. The variation operator which produced the best schedules for the above mentioned objective functions involved using a logic function to switch the tardiest job in the queue. Through the implementation of this variation operator schedules with zero tardiness were obtained. This research provides basis for the implementation of metaheuristics in scheduling for other machine layout models, as it proved the effectiveness of simulated annealing by producing schedules that entirely fulfilled the objective.